Peran Bermain Bagi Perkembangan Kognitif dan Sosial Anak - Tameon, Sance Mariana (Universitas Persatuan Guru 1945 NTT, 2018)
The study was conducted to find out the role of playing in the development of cognitive ans social of students. Qualitative approach was used in this study with teachers and students as the research sucjects. Moreover, to obtain the data, interviews and observations were conducted. The result of the study shows that playing is the childrenâ€™s right which should be met by parents, teachers, society, and government. Through playing children practically may learn to live together since the learn to give and shareÂ whit other children which from time to time can minimize their selfishness. Furthermore, the concept of learning to do is at the same time experienced by them while playing because they may develop imaginations from toys they have of playing with their individual concept.